Damage potential and control of the common mormon butterfly, Papilio polytes Cramer on citrus - Khan, MMH; Molla, MN (Journal of the Asiatic Society of Bangladesh, Science, 2021)
Studies were conducted to know the damage potential and effect of insecticides on leaf area feeding and larval mortality of the common Mormon butterfly, Papilio polytes Cramer in the homestead garden and germplasm center of the Patuakhali Science and Technology University (PSTU) campus and in the laboratory, Department of Entomology, PSTU, Patuakhali, Bangladesh during October to December 2016. Ten Citrus host plants such as Kagoji lime-BAU-1, BAU-2, BAU-3, BAU-4, BARI kagoji, elachi lime, sweet orange, orange, jamir and pumelo were used as study materials. To determine the effects of insecticides on leaf area feeding and larval mortality, five treatments viz., T1 = Voliam flexi 300SC @ 0.5 ml/l of water, T2 = Voliam flexi 300SC @ 1.0 ml/l of water T3 = Bioneem Plus @ 0.5 ml/l of water, T4 = Bioneem Plus @ 1.0 ml/l of water T5 = control were applied. Under natural field conditions, the highest percentage of leaf infestation was recorded in orange, followed by BAU-3, BAU-4, malta and elachi lime, while the lowest percentage was in BARI kagoji on 23 and 30 November, 2016. At the top canopy, the highest percentage of leaf infestation was recorded in orange and elachi (56%), while the lowest was in BAU-4 (8%). At the middle canopy, the highest percentage of leaf infestation was recorded in orange (56%), while the lowest was in jambura (12%). At the lower canopy, the highest percentage of leaf infestation was recorded in BAU-3 (40%), while the lowest was in elachi (8%). At the top canopy, significantly the highest percentage of infested leaves per branch was observed in orange (51.39%) and the lowest percentage of infested leaves per branch was in BAU-4 kagoji lime (10.86%). At middle and lower canopies, no significant difference was observed in the percentage of infested leaves per branch among different citrus varieties. The lowest percentage (6%) of leaf area consumed by 4th instar larva was recorded in T2 (Voliam flexi 300SC @ 1.0 ml/l of water) treated leaf, while the highest percentage of leaf area consumption was found in T5 (control) at 3 HAT. The highest percent mortality (100%) of larvae was found in T2 treated citrus plant, while the lowest percent mortality was in the T3 (70%) treated plant. No mortality was recorded in the untreated control (T5) plant. J. Asiat. Soc. Bangladesh, Sci. 47(1): 35-46, June 2021